Radio As An Alternative Solution In Pandemic Covid-19 In The Border Region Of Sanggau District, West Kalimantan - Iwan Ramadhan (Institut Agama Islam Negeri (IAIN) Bone, 2021)
The government's efforts to control the spread of the Covid-19 virus by issuing various policies, one of which is learning from home. Schools were closed, and learning methods were changed using the online system. However, there are many findings in its application, such as facts on networks/internet quotas and teachers' readiness in online learning. One of the problematic areas is a school on the border of Sanggau Regency, West Kalimantan. Therefore an innovative solution is needed to overcome this problem, one of which is radio use in collaboration with the RRI station. This study aimed to describe radio as an alternative in learning in the border area of Sanggau Regency in collaboration with RRI Station. The method used is qualitative, with interviews and literature study based on trusted news. The result of this research is that an alternative learning media using radio in collaboration with RRI as an alternative to Covid-19 distance learning is quite effective in solving difficult network solutions in border areas.Upaya pemerintah dalam mengendalikan penyebaran virus Covid-19 dengan mengeluarkan berbagai kebijakan, salah satunya belajar dari rumah. Sekolah ditutup dan metode pembelajaran diubah menggunakan sistem online. Namun dalam implementasinya banyak ditemukan kendala, seperti ketersediaan fasilitas jaringan / kuota internet, kesiapan guru dalam pembelajaran online. Salah satu daerah yang mengalami kendala tersebut adalah sekolah di perbatasan Kabupaten Sanggau, Kalimantan Barat, oleh sebab itu perlu adanya solusi yang inovatif untuk mengatasi permasalahan tersebut, salah satunya adalah penggunaan radio yang bekerja sama dengan stasiun RRI. Tujuan penelitian ini adalah mendeskripsikan mengenai radio sebagai alternatif dalam pembelajaran di kawasan perbatasan Kabupaten Sanggau bekerja sama dengan Stasiun RRI. Metode yang digunakan adalah kualitatif dengan wawancara dan studi pustaka berdasarkan berita-berita yang terpecaya. Hasil penelitian ini adalah alternatif media pembelajaran mennggunakan radio yang bekerja sama dengan RRI sebagai alternatif pembelajaran jarak jauh ditengah pandemi Covid-19 terbilang cukup efektif dalam memecahkan solusi jaringan yang sulit di daerah perbatasan.